Contratista independiente y trabajo subordinado - Buenahora, Manuel; Gómez Naranjo, Abelardo; Jaramillo Giraldo, José; Rincón Lara, Camilo; García Merlano, Jorge (Estudios de Derecho, 1957)
Contratista independiente y trabajo subordinado